Relationship Quality Of Health Services With Patient Satisfaction At Lancirang Health Center - Alfinia, Mesyia; Sulaiman, Zulkarnain; Adri, Khaeriyah (Tadulako University, 2025)
ABSTRACT Patient satisfaction is an important indicator in assessing the success of health services, which is not always in line with the quality of services provided. In Lancirang Health Center itself, although the quality of service is relatively good, patient satisfaction in 2023 only reached 63.3%, still below the national target of 95%. This study aims to determine the relationship between the quality of health services consisting of five dimensions (reliability, assurance, tangible evidence, empathy, and responsiveness) with patient satisfaction. This study uses the quantitative method with a cross-sectional design. The random sampling technique was used with a total of 218 respondents. Data were collected through observation, questionnaires, interviews, and documentation, then analyzed using the chi-square test. The results showed that each dimension of service quality had a significant relationship with patient satisfaction, with a p value <0.05. The reliability dimension showed that 96.2% of patients who considered the service reliable were satisfied. Likewise, in the dimensions of assurance, tangible evidence, empathy, and responsiveness, the majority of respondents who rated the service as good in each of these aspects were satisfied. These findings suggest that the service received by patients has a direct effect on their satisfaction. The authors found that there was a statistically significant correlation between health service quality and patient satisfaction at Lancirang Health Center.